2022
DOI: 10.3390/ijms23105754
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Landscape of UPL5-Ubiquitinated on Multiple Subcellular Components of Leaf Senescence Cell in Arabidopsis

Abstract: Catabolism of macromolecules is a major event in senescent cells, especially involving proteolysis of organelles and abnormally aggregated proteins, circulation of nutrients, and precise control of intracellular environmental balance. Proteasomes are distributed in the nucleus and cytoplasm; however, proteasomes in organelles are limited. In this study, multi-omics proteomic analyses of ubiquitinated proteins enriched by using antibody against “di-Gly-Lys” via a free labeling were used to investigate the globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Previous ubiquitomic analysis of the upl5 mutant relative to WT found that WHY2 protein was a candidate substrate for UPL5-mediated ubiquitination. 36 To further demonstrate this interaction, we first performed a yeast two-hybrid assay. UPL5-BD and WHY2-AD plasmids were co-transformed in yeast strain AH109, and the growth of the co-transformants on the deficient TRP/ADE/HIS/LEU medium indicated that UPL5 interacted with WHY2 in the yeast cell ( Figures 1 A and 1B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous ubiquitomic analysis of the upl5 mutant relative to WT found that WHY2 protein was a candidate substrate for UPL5-mediated ubiquitination. 36 To further demonstrate this interaction, we first performed a yeast two-hybrid assay. UPL5-BD and WHY2-AD plasmids were co-transformed in yeast strain AH109, and the growth of the co-transformants on the deficient TRP/ADE/HIS/LEU medium indicated that UPL5 interacted with WHY2 in the yeast cell ( Figures 1 A and 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Using tobacco leaf transient injection and Arabidopsis protoplast transformation, we showed that the full-length WHY2 interacted with UPL5 in mitochondria and the nucleus, the deleted mitochondrion transit peptide (mtp) version of WHY2 interacted with UPL5 in chloroplast, the deleted chloroplast transit peptide (ctp) version of WHY2 interacted with UPL5 in cytoplasm and nucleus as well as mitochondria ( Figures 1 D-1F), while single, full-length UPL5 fused GFP was detected in the nucleus, plastid, mitochondria, or cytoplasmic compartments. 36 , 37
Figure 1 Interaction of UPL5 and WHY2 colocalized in chloroplasts and nucleus, as well as mitochondria (A) Variants of WHY2 proteins in yeast two hybrid system. (B) Co-transformation of UPL5 and WHY2 variants in yeast cells was selected in medium deficient for Trpton (Trp), Hisdine (His), Adenine (Ade), and Leucine (Leu).
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations